Caracterización y relacion clonal de cepas de enterococos aisladas de alimentos de origen animal de un área rural del centro de la provincia de Buenos Aires, Argentina - Pourcel, Natalia Gisela (2018)
Enterococci are microorganisms that are widely found distributed in the environment. They make up the usual microbiota of the tract gastrointestinal system of man and animals, plants and environment. The objective of this thesis work was to carry out a level identification genotypic strain of Enterococcus spp. isolated from foods of animal origin from a rural area in the center of the Province of Buenos Aires and establish its clonal relationship with strains isolated from invasive infections human resources corresponding to the same period of time and geographic space. The phenotypic and genotypic characterization of 125 isolates was performed belonging to the genus Enterococcus recovered from foods of origin meat and dairy products in the period between January and December 2013. The species most frequently identified by molecular method was E. faecalis (75.2%), E. faecium (19.2%), E. raffinosus (2.4%), E. durans (1.6%), E. gallinarum (0.8%) and E. avium (0.8%). The following genes were investigated by molecular amplification vancomycin resistance (VAN): vanA, vanB, vanC, vanD, vanE and vanG. The gen vanA was detected in three isolates corresponding to E. faecium: dry craft sousage, cow's cheese and sheep's cheese detected the vanA gene in the other Enterococcus species. In E. gallinarum, isolated from dry craft sousage the presence of vanC was observed. In the isolations recovered from food the genes, vanB, vanD, vanE and vanG were not detected. Resistance to glycopeptides (VAN, TEI) using resistance tests phenotypic antimicrobial agents (determination of MIC, by dilution method in agar) and molecular amplification was concordant in all isolates analyzed. 2.4% of the isolates showed a high level of resistance to gentamicin (HLRG). All of the isolates were E. faecalis obtained from meat foods. Experiments were carried out bacterial conjugation in vitro between E. faecalis with HLRG (donors) and strain E. faecalis JH2-SS of human origin with chromosomal resistance to streptomycin (receptor) and without HLRG. After conjugation experiment, the recipient strain E. faecalis JH2-SS migrated with a relative mobility value similar to that of the donor cell, indicating that the incorporation of the plasmid occurred in a similar position and the acquired plasmid. The presence of transferable resistance was demonstrated in strains of E. faecalis with HLRG and E. faecium with high level of resistance to VAN. Another possible path of resistance dissemination was also tested antimicrobial through the mobilization and adaptation of certain clones of Enterococci present in food to patients and the hospital environment. Through studies of PFGE, clonal relationship between strains of E. faecalis with HLRG of human origin and food. In Argentina, this is the first evidence of clonal dissemination of strains in foods of animal origin and human.